The impact of state policy on teen dating violence prevalence. (October 2015) - Hoefer, Richard; Black, Beverly; Ricard, Mark
Abstract: Teen dating violence (TDV) is a serious public health concern that is associated with many negative effects. Studies on TDV prevention most often focus on the evaluation of prevention programs in school and community settings. Much less is known about the effects of policy on TDV prevalence. This study tests a model to explain whether stronger laws regarding TDV, specifically civil protection orders, have an impact on TDV rates in states. Results show that stronger policy, Democratic party control of the governor's office, and higher state median income are associated with lower rates of TDV. This study provides solid information regarding the role of civil protection orders as a means of TDV prevention and adds to our knowledge of the efficacy of state-level TDV policy. The information can lead to increased vigor on the part of advocates to strive for specific provisions in the law and to work for gubernatorial candidates who will support such laws.